2021
DOI: 10.1016/j.medj.2021.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Real-time analysis of a mass vaccination effort confirms the safety of FDA-authorized mRNA COVID-19 vaccines

Abstract: McMurry et al. assess the real-world safety of the BNT162b2 and mRNA-1273 COVID-19 vaccines. Using natural language processing, they compare the rates of specified adverse effects between 68,266 vaccinated individuals and 68,266 matched unvaccinated individuals. They find that both vaccines are safe and tolerated in clinical practice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 29 publications
2
66
0
2
Order By: Relevance
“…Previous research has shown the importance of active solicitation of information [68] and EMRs are now being used to help evaluate the effectiveness [69] and potential side effects [70,71] of COVID-19 vaccines. Similarly, EMR-based data has been utilized previously in studies looking at the effects of the COVID-19 pandemic as a stressor on people with bipolar disorder [72], the safety of the COVID-19 vaccine in pregnant women [73], the effect of COVID-19 on pregnancy outcomes [74], the effects of clinical characteristics on outcomes of COVID-19 patients [75][76][77], the factors that influence pharmacotherapy for tobacco dependence in the VA system [78], the effect of mental health disorders on COVID-19 mortality [79], COVID-19 vaccine adverse effects [68], and the effects of the COVID-19 pandemic on body mass index in children [80]. Thus, the present study builds upon a growing body of research examining similar effects of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown the importance of active solicitation of information [68] and EMRs are now being used to help evaluate the effectiveness [69] and potential side effects [70,71] of COVID-19 vaccines. Similarly, EMR-based data has been utilized previously in studies looking at the effects of the COVID-19 pandemic as a stressor on people with bipolar disorder [72], the safety of the COVID-19 vaccine in pregnant women [73], the effect of COVID-19 on pregnancy outcomes [74], the effects of clinical characteristics on outcomes of COVID-19 patients [75][76][77], the factors that influence pharmacotherapy for tobacco dependence in the VA system [78], the effect of mental health disorders on COVID-19 mortality [79], COVID-19 vaccine adverse effects [68], and the effects of the COVID-19 pandemic on body mass index in children [80]. Thus, the present study builds upon a growing body of research examining similar effects of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…4 Additional real-world retrospective studies in major health systems in the United States and Israel further support the effectiveness and safety of these vaccines. [5][6][7] However, only about 50% of the United States population is fully vaccinated as of July 2021, with an even lower fraction fully vaccinated across the globe. 2 Further, there have been reports of reduced vaccine effectiveness against emerging variants and local increases in COVID-19 cases despite mass vaccination, raising questions about the potential need to administer vaccine booster doses and to develop variant-targeted vaccines in the future.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 These advances have enabled the rapid assessment of the real-world effectiveness and safety of the messenger RNA (mRNA) vaccines mRNA-1273 (Moderna) and BNT162b2 (Pfizer/BioNTech) as well as a targeted investigation of the incidence of cerebral venous sinus thrombosis among patients receiving COVID-19 vaccines (including Ad26.COV2.S) within the Mayo Clinic Health System. [6][7][8] We believe such approaches are essential for the development and deployment of vaccines and, most importantly, to build trust and transparency for the public. Here, we expand on this effort to conduct a preliminary assessment of the effectiveness of the Ad26.COV2.S vaccine using EHR data from the Mayo Clinic and Mayo Clinic Health System between February 27 and July 22, 2021.…”
Section: Introductionmentioning
confidence: 99%